وضعية الإحالة على الاستيداع بين الممارسة وقيد ضرورة المصلحة - عتيقة, معاوي; رؤوف, بوسعدية (University of Eloued جامعة الوادي, 2020)
تعد وضعية الإحالة على الاستيداع من الموضوعات المهمة، إذ تؤدي إلى تعليق العلاقة الوظيفية التي تربط الموظف بالإدارة بصفة مؤقتة، وذلك نظرا للظروف غير المتوقعة التي قد تصادف حياة الموظف الخاصة . وعليه، سنقو م من خلال هذه الورقة البحثية، ببيان كيف تعد ضرورة المصلحة قيدا يقع على عاتق الموظف وتحد من حريته في ممارسة هذا الحق المتأرجح الطبيعة بين الإجباري على الإدارة وبين كونه اختياريا؟ The referral to availability status is one of the important topics, because it leads to a temporary suspension of the functional relationship between the employee and the administration due to the unexpected circumstances that may encounter the emplyee in his life. Consequently, through this research paper, we will show how the necessity of service is considered as a constraint imposed on the emloyee, and how it limits his freedom to benefit from this ambivalent rightbetween what is compulsory for the administration and other times optional.
مجلد11، عدد1
Keywords: الإحالة على الاستيداع، الموظف، ممارسة، قيد، ضرورة المصلحة، مصلحة الموظف; Referral to Availability; Emplyee; Practice; Constraint; Necessity of Service ; Employee’s interest.